Self-Reflexivity and Meta-Poetry in Billy Collins’ Selected Poems - al-Zubbaidi, Haitham Kamil (Al-Adab Journal, 2015)
Although postmodernism is known for its tendency to deconstruct the basics of existing traditions and conventions pertaining to existing literary forms, among other realms, and though it is commonly associated with self-reflexivity, self-consciousness, self-referentiality and introspective interests, there are numerous examples in the postmodern literary oeuvre of many poets and writers, which prove, whether by fecundity or by frequency, that there is an underlying orientation to establish this self-reflexivity as a new convention, endow it with rules and present it as a post-modernist tradition. In this sense, the apparent postmodernist claim to deconstruct and eradicate the deep-rooted literary conventions implies persisting attempts to develop other conventions based on criticizing, ridiculing and abolishing the former. This paper aims to prove the assumption given above by means of investigating and analyzing some poems of Billy Collins (1941- ) whose main theme and subject matter is self-reflexivity